Initial Luck, Status-Seeking and Snowballs Lead to Corporate Success and Failure - Amihai Glazer; Vesa Kanniainen; Panu Poutvaara (Institute for the Study of Labor (IZA), 2004)
Corporate success often resembles a snowball. We show how initial luck in hiring talented people, the resulting technological advantage, superior corporate culture, and status-seeking by workers can make small initial differences generate large differences over time.
Keywords: L00; L13; 330; industry equilibrium; initial luck; status effects; snowball; Unternehmensentwicklung; Prestige; Unternehmenskultur; Evolutionsökonomik; Innovationswettbewerb; Theorie; path dependency